Calling for Multiculturalism-Based Communication Campaign in Early Prevention of Youth Diabetes: Examination of Contemporary Indonesia - Andi Windah; Yulianto; Ida Nurhaida; Nina Yudha Aryanti; Andy Corry W (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The increasing incidence of type 2 diabetes mellitus (DMT2) among Indonesian adolescents has prompted the consideration of early detection and management in school-age individuals. One contributing factor is the spatial shift phenomenon, where rural and urban areas in Indonesia are becoming more connected, leading to a uniform market for food and beverage options that pose a higher risk of developing diabetes. This study examines three key aspects of Indonesia's ethnically diverse youth population: their lifestyle, use of information technology, and dietary choices. These factors significantly impact their likelihood of consuming foods and beverages that are harmful for individuals with diabetes. The study, conducted using a library-centric research approach, reveals that Indonesian youths' daily routines blend traditional and modern cultural practices which profoundly influenced by technological advancements, social media prevalence, and globalization. Interestingly, the findings highlight that no communication campaigns have been launched to address diabetes prevention among Indonesian adolescents from a multicultural perspective. The research also found that it is crucial for DMT2 prevention initiatives to develop effective strategies that can penetrate the subconscious mindset of individuals living in urban and rural areas while considering Indonesia's diverse cultural context. Efforts should be made to raise awareness and provide guidance tailored to different cultural backgrounds to combat the rising problem of diabetes among Indonesian youth.